L-selectin dimerization enhances tether formation to properly spaced ligand - Dwir, Oren; Schwarz, Ulrich S. (The journal of biological chemistry, 2002)
Selectin counterreceptors are glycoprotein scaffolds bearing multiple carbohydrate ligands with exceptional ability to tether flowing cells under disruptive shear forces. Bond clusters may facilitate formation and stabilization of selectin tethers. L-selectin ligation has been shown to enhance L-selectin rolling on endothelial surfaces. We now report that monoclonal antibodies-induced L-selectin dimerization enhances L-selectin leukocyte tethering to purified physiological L-selectin ligands and glycopeptides. Microkinetic analysis of individual tethers suggests that leukocyte rolling is enhanced through the dimerization-induced increase in tether formation, rather than by tether stabilization. Notably, L-selectin dimerization failed to augment L-selectin-mediated adhesion below a threshold ligand density, suggesting that L-selectin dimerization enhanced adhesiveness only to properly clustered ligand. In contrast, an epidermal growth factor domain substitution of L-selectin enhanced tether formation to L-selectin ligands irrespective of ligand density, suggesting that this domain controls intrinsic ligand binding properties of L-selectin without inducing L-selectin dimerization. Strikingly, at low ligand densities, where L-selectin tethering was not responsive to dimerization, elevated shear stress restored sensitivity of tethering to selectin dimerization. This is the first indication that shear stress augments effective selectin ligand density at local contact sites by promoting L-selectin encounter of immobilized ligand.
Gesehen am 15.12.2017